2020
DOI: 10.1038/s41598-020-64058-5
|View full text |Cite
|
Sign up to set email alerts
|

Familiarity with humans affect dogs’ tendencies to follow human majority groups

Abstract: Recently, copying others' behaviour has attracted attention among researchers. It aids individuals in reducing uncertainty about the knowledge of the environment and helps them in acquiring an adaptive behaviour at a lower cost than by learning it by themselves. Among the copying strategies, conformity, which is the copying of behavioural decisions presented by the majority, has been well studied and reported in many animals, including humans. The previous study showed that dogs did not conform to their multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Dogs follow not only the gaze but also the movements of humans. When there were two bowls with food, dogs followed the one that more humans went to under certain conditions (Nagasawa et al, 2020). Dogs chose the same container they had seen humans choose, even if they had seen the human removing food from it and pretending to eat it (Chijiiwa et al, 2020).…”
Section: Gaze Communication For Dogsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dogs follow not only the gaze but also the movements of humans. When there were two bowls with food, dogs followed the one that more humans went to under certain conditions (Nagasawa et al, 2020). Dogs chose the same container they had seen humans choose, even if they had seen the human removing food from it and pretending to eat it (Chijiiwa et al, 2020).…”
Section: Gaze Communication For Dogsmentioning
confidence: 99%
“…Used human pointing in the task of selecting one of two containers Miklosi et al, 2005 Used human pointing in the task of selecting one of two containers Miklosi et al, 2005 Used human gaze direction with pointing in the task of selecting one of two containers Hare et al, 2002 Looked in the direction indicated by human gaze (with head movements) Pongrácz et al, 2019 Looked in the direction directed by human gaze (with head movements) Agnetta et al, 2000;Hare et al, 1998;Met et al, 2014;Téglás et al, 2012 Followed the container that humans visited in a situation with two food containers Chijiiwa et al, 2020 Followed the container that humans visited in a situation with two food containers Chijiiwa et al, 2020;Nagasawa et al, 2020 Social reference…”
Section: Bond Formation Between Dogs/cats and Humansmentioning
confidence: 99%
“…This may be contrary to what has been found in dogs. Dogs differed in their compliance with operant cues from familiar versus unfamiliar people, and the owner was markedly more effective than strangers in calming dogs during fearful situations [55] and decision-making [56]. However, in less challenging experimental environments, social familiarity seems less important for dogs [57].…”
Section: Discussionmentioning
confidence: 98%
“…Used human pointing in the task of selecting one of two containers Miklosi et al, 2005 Used human pointing in the task of selecting one of two containers Miklosi et al, 2005 Used human gaze direction with pointing in the task of selecting one of two containers Hare et al, 2002 Looked in the direction indicated by human gaze (with head movements) Pongrácz et al, 2019 Looked in the direction directed by human gaze (with head movements) Hare et al, 1998;Agnetta et al, 2000;Téglás et al, 2012;Met et al, 2014 Followed the container that humans visited in a situation with two food containers Chijiiwa et al, 2020 Followed the container that humans visited in a situation with two food containers Chijiiwa et al, 2020;Nagasawa et al, 2020 Social reference…”
Section: A Corrigendum Onmentioning
confidence: 99%